Anaylsis of specific impulsive force in electrical discharge machining - Woo, Victor Yuming. (2011)
One of the useful applications of electrical Discharge Machining (EDM) is the fabricating of thin wall structures due to the absence of physical contact between the tool and workpiece. However, the presence of impulsive force exists in the sparking process due bubble implosion caused by the sudden pressure drop in the plasma channel. This could give rise to limitations in thickness of the thin wall. This project shall look into the effects of specific impulsive force with discharge energy. Experimental results showed that specific impulsive force did not change much at discharge energy below 3000 µJ. However, as the input energy increases above 3000 µJ, changes in specific impulsive force became more prominent. Also, higher fluctuations in the results obtained for specific impulsive force above 3000 µJ were observed. Taguchi method together with Analysis of Variance (ANOVA) was used to determine the effects of various machining parameters on specific impulsive force. Through ANOVA, it was observed that discharge energy was the most significant factor for the specific impulsive force. The effects of specific impulsive force on thin wall structure were studied through determining the critical wall thickness for various discharge energy. Experimental work showed that both melting and specific impulsive force were responsible for the critical wall thickness in EDM. As the thickness of the wall falls below the critical wall thickness for the respective discharge energy, brink erosion at the wall was observed.